Nickel adsorption onto carbon anode dust modified by acetic acid and KOH - Štrkalj A.; Rađenović A.; Malina J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Carbon anode dust (CAD) is metallurgical waste material of aluminium production industry. The objective of this study was to convert carbon anode dust to acetic acid-modified and KOH-modified carbon adsorbat. Modified and unmodified carbon anode dust samples were characterized by SEM analysis. Pore volume, pore size and surface area were determined with BET method. The prepared carbons were evaluated for their adsorption capacity of nickel ions. The experimental data were analyzed by Freundlich and Langmuir isotherms. Changes in the surface morphology, surface area properties and obtained adsorption capacity indicate that acetic acid is a better modifier than KOH. Equilibrium results showed that acetic acid modification increased the CAD adsorption capacity for Ni (II) more than KOH modification.